2011
DOI: 10.5586/asbp.2011.040
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of seed banks during secondary succession on poor soils

Abstract: IntroductionIn the second half of the 20th century new technologies introduced in Europe, and withdrawal from conventional techniques of plant and animal production caused a marked decrease in agriculturally used area. Secondary succession was initiated on gradually abandoned fields and pastures, unmown meadows and forests after modified use (theory and prediction -[1], abandoned cattle grazing -[2-6], post-fire succession on abandoned fields [7]). During last two decades many studies were published on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…These results conform to the dominant paradigm of “declining seed numbers and diversity and decreasing similarity between seed bank and aboveground vegetation as succession proceeds” ( Thompson, 2000 ). Many results obtained from recent studies also support the pattern of declining seed density and similarity with plant community succession ( Shen et al, 2007 ; Kwiatkowska-Falińska, Jankowska-Blaszczuk & Wódkiewicz, 2011 ; Egawa & Tsuyuzaki, 2013 ; Kiss et al, 2017 ). In the complete chronosequence of secondary succession in the karst landscape, aboveground ephemeral and perennial herbs were dominant in terms of both individual density and species richness at early stages.…”
Section: Discussionmentioning
confidence: 71%
“…These results conform to the dominant paradigm of “declining seed numbers and diversity and decreasing similarity between seed bank and aboveground vegetation as succession proceeds” ( Thompson, 2000 ). Many results obtained from recent studies also support the pattern of declining seed density and similarity with plant community succession ( Shen et al, 2007 ; Kwiatkowska-Falińska, Jankowska-Blaszczuk & Wódkiewicz, 2011 ; Egawa & Tsuyuzaki, 2013 ; Kiss et al, 2017 ). In the complete chronosequence of secondary succession in the karst landscape, aboveground ephemeral and perennial herbs were dominant in terms of both individual density and species richness at early stages.…”
Section: Discussionmentioning
confidence: 71%
“…It was found that the increase in litter was positively correlated with the total seed bank density, and cryptogam biomass was negatively correlated with the seed bank of weedy species. It was argued by Kwiatkowska‐Falińska et al () that the high cover of cryptogams as an effective seed trap can mitigate the speed or even prevent the arrival of seeds on the soil surface and thus their incorporation into the soil seed bank, which is one likely explanation for the correlation found between cryptogam biomass and the seed bank density of weedy species. For litter it was published in the literature that accumulated litter can also act as a seed trap for grassland species (Donath & Eckstein ; Ruprecht & Szabó ), but can help retain soil humidity and decrease the temperature fluctuations on the soil surface which can have positive effects on the preservation of soil seed banks, especially in dry communities (Eckstein & Donath ).…”
Section: Discussionmentioning
confidence: 99%